The end of growth adapting to our new economic reality - Heinberg, Richard (Tantor, 2011)
Economists insist that recovery is at hand, yet unemployment remains high, real estate values continue to sink, and governments stagger under record deficits. The End of Growth proposes a startling diagnosis: humanity has reached a fundamental turning point in its economic history. The expansionary trajectory of industrial civilization is colliding with non-negotiable natural limits.
Keywords: Economic Growth